2019
DOI: 10.1074/jbc.ra118.006229
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid substitutions in the human homomeric β3 GABAA receptor that enable activation by GABA

Abstract: Edited by Roger J. Colbran GABA A receptors (GABA A Rs) are pentameric ligand-gated ion channels that mediate synaptic inhibition throughout the central nervous system. The ␣ 1 ␤ 2 ␥ 2 receptor is the major subtype in the brain; GABA binds at the ␤ 2 (؉)␣ 1 (؊) interface. The structure of the homomeric ␤ 3 GABA A R, which is not activated by GABA, has been solved. Recently, four additional heteromeric structures were reported, highlighting key residues required for agonist binding. Here, we used a protein engi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
0
4
1
Order By: Relevance
“…It is known that β subunits can form the spontaneously active (i.e., without GABA) homomers (Blair et al, 1988;Cestari et al, 1996;Wooltorton et al, 1997), which could contribute to the observed spontaneous activity. However, it needs to be stressed that functional homomers were demonstrated for the β 3 (Connolly et al, 1996;Davies et al, 1997;Wooltorton et al, 1997;Gottschald Chiodi et al, 2019) and β 1 (Sigel et al, 1989;Sanna et al, 1995;Krishek et al, 1996;Miko et al, 2004) subunits, whereas in the present study, β 2 subunits were expressed. Moreover, the expression level of putative β subunit homomers is expected to be the same in the case of WT and the mutants, and the spontaneous activity in the case of the WT receptors was negligible indicating that contribution from the β homomers is low if any.…”
Section: Discussioncontrasting
confidence: 48%
“…It is known that β subunits can form the spontaneously active (i.e., without GABA) homomers (Blair et al, 1988;Cestari et al, 1996;Wooltorton et al, 1997), which could contribute to the observed spontaneous activity. However, it needs to be stressed that functional homomers were demonstrated for the β 3 (Connolly et al, 1996;Davies et al, 1997;Wooltorton et al, 1997;Gottschald Chiodi et al, 2019) and β 1 (Sigel et al, 1989;Sanna et al, 1995;Krishek et al, 1996;Miko et al, 2004) subunits, whereas in the present study, β 2 subunits were expressed. Moreover, the expression level of putative β subunit homomers is expected to be the same in the case of WT and the mutants, and the spontaneous activity in the case of the WT receptors was negligible indicating that contribution from the β homomers is low if any.…”
Section: Discussioncontrasting
confidence: 48%
“…An estimation of the binding free energy (scoring function) of the protein‐ligand complex was conducted, along with a comparison of the number of H‐bonds formed between protein and ligand atoms. The quality of the final model was assessed using ICM Molsoft standard docking procedure against non‐benzodiazepine compounds [50, 51]. Since our search algorithm was adapted based on Z‐drugs, we proceeded to screen another segment of the reference set, comprising 90 active compounds (<1 μM) from the ChemblDB, through the docking model to estimate the degree of selectivity [52].…”
Section: Methodsmentioning
confidence: 99%
“…Since long-term imbalances in these metabolites can lead to brain diseases [5], an understanding of the regulation of GABA uptake is necessary. The GABA-A receptor is a quintessential ligand-gated ion channel that mediates synaptic inhibition throughout the central nervous system [6]. After GABA performs its action as a neurotransmitter, it is reabsorbed into the presynaptic neurons and neural bridges [7].…”
Section: Cellular Function Of Gaba In the Brainmentioning
confidence: 99%